Jesus tradition in the Apostolic Fathers: their explicit appeals to the words of Jesus in light of orality studies - Young, Stephen E. (Wissenschaftliche Untersuchungen zum Neuen Testament / 2, 2011)
This dissertation reevaluates the tradition of Jesus' sayings in the Apostolic Fathers in light of the growing recognition of the impact of orality upon early Christianity and its writings. At the beginning of the last century it was common to hold that the Apostolic Fathers made wide use of the canonical Gospels. While a number of studies have since called this view into question, many of them simply replace the theory of dependence upon canonical Gospels with one of dependence upon other written sources. No full-scale study of Jesus tradition in the Apostolic Fathers has been published which takes into account the last four decades of new research into oral tradition in the wake of the pioneering work of Milman Parry and Albert Lord. Based on this new research, the present dissertation advances the thesis that an oral-traditional source best explains the form and content of the explicit appeals to Jesus tradition in the Apostolic Fathers that predate 2 Clement. In the course of the discussion, attention is drawn to the ways in which the Jesus tradition in the Apostolic Fathers informs our understanding of the use of oral tradition in Christian antiquity